2006
DOI: 10.1111/j.1600-6143.2005.01186.x
|View full text |Cite|
|
Sign up to set email alerts
|

Low Molecular Weight Dextran Sulfate: A Strong Candidate Drug to Block IBMIR in Clinical Islet Transplantation

Abstract: The instant blood-mediated inflammatory reaction (IBMIR) is triggered in clinical islet transplantation when human pancreatic islets come in contact with blood and may explain the initial tissue loss associated with this procedure. Low molecular weight dextran sulfate (LMW-DS; MM 5000), today available for clinical use, inhibits both complement and coagulation activation. In a tubing loop model, LMW-DS at concentrations ranging from 0.01 to 1 g/L showed a dose-dependent inhibition of IBMIR with an inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 37 publications
1
95
0
Order By: Relevance
“…Recently, the maximum tolerated doses of DXS were determined in vivo in cynomolgus monkeys and i.v. or intraportal bolus injections of 3-6 mg/kg, followed by continuous infusion of 0.3-1.2 mg/kg/h for 6 h, and appeared to be safe (50). It should also be considered, however, that DXS binds to the surface of activated endothelial cells (3), which may limit the plasma concentration available for its inhibitory effect on DC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the maximum tolerated doses of DXS were determined in vivo in cynomolgus monkeys and i.v. or intraportal bolus injections of 3-6 mg/kg, followed by continuous infusion of 0.3-1.2 mg/kg/h for 6 h, and appeared to be safe (50). It should also be considered, however, that DXS binds to the surface of activated endothelial cells (3), which may limit the plasma concentration available for its inhibitory effect on DC.…”
Section: Discussionmentioning
confidence: 99%
“…3,[16][17][18] However, it is difficult to apply these anticoagulants in the clinical environment because systemic administration is associated with an increased risk of severe bleeding. 19 Therefore, there is an urgent need to explore new therapeutic target for treating IBMIR with fewer bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…Ikada et al [47] developed a bio-artificial pancreas (encapsulated islets) using LMW-DS and succeeded in preventing complement attack. The Korsgren group revealed that LMW-DS is useful in preventing instant blood-mediated inflammatory reaction (IBMIR: a rapid thrombotic reaction, in which binding of platelets to the islet surface, activation of the coagulation and complement systems, and leukocyte infiltration of the islets when the islets are exposed to blood occur) [48][49][50] . Various materials have been studied and shown to have positive results, but encapsulated islets that can be utilized permanently have not been developed yet.…”
Section: Resultsmentioning
confidence: 99%
“…However, several recent studies have clearly shown that most of the islets (approximately 60% islets) transplanted intraportally are immediately destroyed, mainly due to the IBMIR [49,70] . Moreover, the infusion of islets with some other pancreatic tissues 23 February 15, 2012|Volume 3|Issue 1| WJGP|www.wjgnet.com (acinar cells, ductal cells or connective tissues) in the portal vein always has a risk of causing portal hypertension and portal vein embolization [71] .…”
Section: Ideal Transplantation Site For Encapsulated Isletsmentioning
confidence: 99%